SOCIAL ADAPTATION AND PSYCHOLOGICAL REHABILITATION AS A MEANS OF PRESERVING SOCIAL CAPITAL OF COMBATANTS - Hordiienko, Ye. (Pressing Problems of Public Administration, 2019)
Any political crisis complicated by hostilities has a number of social consequences. The destructive impact of war complicates the link between socialization processes and social capital, impedes its preservation and restoration, and future development of the country. It is because of the specific nature of military activity and the impact of war on the individual that the combatants need increased care and support. Therefore, the purpose of the article is to analyze the impact of psychological rehabilitation and social adaptation measures on the preservation of social capital of combatants. Social capital is a kind of social and psychological resource of combatants, which allows to maintain absolute trust in one another, group identity, cohesion, and makes it possible not to lose sense of living and self-identity. The main purpose of social rehabilitation is to ensure and provide for socialization of the individual. Social rehabilitation includes a set of actions aimed at restoring health, social status, legal status, moral and psychological balance, self-confidence. Retraining, raising the level of knowledge, retraining allows combatants to be successfully involved in the system of social relations. Currently there are many programs for professional adaptation of combatants, still there is a problem with the lack of a single information platform that would provide a full range of information on existing opportunities for veterans. Employment statistics for demobilized combatants in Ukraine today confirms the low efficiency of government programs. The policy of the state authorities should be aimed at building a comprehensive system of support, creating programs and preferential conditions, investment and innovation activities, intensification of information and educational campaigns for professional adaptation. Psychological rehabilitation is an activity carried out by the subjects of psychological work, aimed at restoring mental functions, personality features and the system of relations of personality of a military man, which allow him to function in a peaceful society. The consequence of not resolving the issue of psychological rehabilitation of combatants may be their maladaptation, which leads to the loss (or decrease) of social capital. Today there are more than 200 state and non-governmental institutions, institutions and organizations operating in the sphere of providing psychological services to combatants funded by local budgets. The Government has introduced a new mechanism for psychological rehabilitation, which should comprehensively provide for the need for psychological rehabilitation. The experience of 2014-2019 has shown that a system of providing rehabilitation services to persons who have through the war is just being developed. Psychological rehabilitation and social adaptation measures after the end of hostilities will continue to be of particular importance for the preservation of social capital of combatants and Ukrainian society as a whole.